Vertical Distribution of Benthic Foraminifera in Sediments in the Waters of Western Rupat Strait Bengkalis Regency, Riau Province - Rica Purnama Sari; Rifardi '; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in May 2014 in the coastal waters of the Western Rupat Strait. The research aimed to determine the distribution patterns of benthic foraminifera and relative velocity of sediments in the Rupat Strait. This research used purposive sampling method which divided location into 3 stations.Benthic foraminifera from 3 stations can be divided into 4 groups. Group I was characterized by Ammonia becarri, Baculogypsina sphaerulata, Bolivina humilis, Bolivina pacifica, Angulogerina angulosa, Bolivina puncata and Cancris auriculus. Group II, was characterized by Textularia schencki, Globorotalia tumida and Loxostomina limbatum. Group III was characterized by Ammonia beccarii and Textularia neoconica. Group IV was characterized by Ammonia beccari and Textularia foliacea. Distribution pattern of benthic foraminifera tended to be clumped. The highest value of L/TL occurred to the north of Rupat Strait, at sampling points 8 and 9 received a supply of sediment from Malacca Strait, L/TL was medium at sampling point 5 and 3. Sampling point 2 which was located at the area south of the Strait of Rupat had a weak current (0.1 m/s) and sampling point 5 which was located far from the coast and influenced the strong currents and tidal estuary 7 of Sungai Mesjid while sampling point close to the tidal currents of Malacca Strait. While L/TL lower in areas affected were strong currents of energy that sampling point 4 (0.13 m/s) and the sampling point 1 was Sungai Mesjid basin, sampling points 1, 3 and 6 which was the mangrove areas.Keyword : Rupat Strait, Sediment, Distribution, Benthic, Foraminifera,